PERMAINAN KARTU BILANGAN SEBAGAI ALAT PERAGAUNTUK MENINGKATKAN MOTIVASI BELAJAR MATEMATIKA SISWA KELAS V SDN 010 UJUNG BATU - Mulyasni (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2016)
This research was motivated by the low learning motivation of fifth-grade students in mathematics at SDN 010 Ujung Batu. The purpose of this classroom action research was to improve students’ motivation in learning mathematics through the use of number card games as learning media. The research was conducted at SDN 010 Ujung Batu for one month, starting in August 2014. The subjects of the study were 30 students of class V. The research instruments consisted of teacher and student activity observation sheets and achievement tests. Based on the results of the research and discussion, it can be concluded that the application of number card games as learning media was able to increase students’ motivation to learn mathematics, particularly on integer material. This improvement was indicated by the increase in students’ learning motivation from 59.9% in the first cycle, which was categorized as fairly good, to 71.3% in the second cycle, which was categorized as good. These results show that the use of number card games as learning media can effectively enhance students’ motivation in learning mathematics.